2019
DOI: 10.20504/opus2019c2526
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogical Use of Visual Feedback for Enhancing Dynamics in Higher Education Piano Learning and Performance

Abstract: The pedagogical use of technology-mediated feedback in a higher education piano studio: an exploratory action case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…In contrast with most part of the previous research that has studied the use of technology to provide different kinds of feedback to improve learning (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Van Der Linden et al, 2011; Wang et al, 2012; Leong and Cheng, 2014; Schlegel and Gregory Springer, 2018), we did not found statistical differences between the amount of improvement at the end of the task between the BF and the BNF group. However, behavioral differences found among the BF group could be the result of an increment of the conscious awareness of their own performance as suggested by Hamond (2017). It is important also to highlight that the demanded task and the feedback provided in this study differs widely compared with previous work which mainly studies pitch accuracy and uses real-time feedback.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast with most part of the previous research that has studied the use of technology to provide different kinds of feedback to improve learning (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Van Der Linden et al, 2011; Wang et al, 2012; Leong and Cheng, 2014; Schlegel and Gregory Springer, 2018), we did not found statistical differences between the amount of improvement at the end of the task between the BF and the BNF group. However, behavioral differences found among the BF group could be the result of an increment of the conscious awareness of their own performance as suggested by Hamond (2017). It is important also to highlight that the demanded task and the feedback provided in this study differs widely compared with previous work which mainly studies pitch accuracy and uses real-time feedback.…”
Section: Discussionmentioning
confidence: 80%
“…The study reported improved pitch accuracy by using the system. Previous research has studied the effect of using different kinds of interfaces and different kinds of feedback in singing voice (Thorpe, 2002; Welch et al, 2004; Wilson et al, 2008; Leong and Cheng, 2014), trombone (Schlegel and Gregory Springer, 2018), piano (Hamond, 2017), and violin (Wang et al, 2012). Although there are differences in the way RTVF may improve performance, most of the previous studies reported beneficial effects of RTVF in learning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes parental companionship important throughout the course. Thus, parents and teachers should collaborate harmoniously, and teachers should innovate customized piano courses based on the educational psychology of children, thereby catering to the healthy development of their mentality (Hamond et al, 2019 ).…”
Section: Application Of DL In Piano Education Of Childrenmentioning
confidence: 99%